Ultrasound Diagnosis of Clavicle Fractures in Newborns: A Systematic Review - Luca Galimberti; Gisella Garbetta; Antonella Poloniato; Rosanna Rovelli; Graziano Barera; Nicola Guindani; Maurizio De Pellegrin (MDPI AG, 2024)
Background: Fractures of the clavicle are the most common birth injury among newborns. Aim of this systematic review was to provide a comprehensive analysis of the role of ultrasound (US) in diagnosing clavicular fractures in neonates. Methods: A systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) using PubMed and Embase, including studies focusing on US in neonatal clavicle fracture. Age at US, number of cases examined by US and X-ray, US and X-ray diagnoses, US probe used, fracture site were systematically extracted. Results: A total of 231 articles were found. We ultimately selected 7 publications that satisfied the inclusion criteria, involving 136 patients examined between 3 days and 3 weeks of age, with 135 confirmed fractures. US was performed on all patients and correctly diagnosed all fractures (135/135, 100%). X-ray was performed on 94/136 patients (69.1%) and correctly diagnosed 89/93 fractures (95.7%). Fracture site was: medial in 2/79, middle in 37/79, and lateral in 40/79. In the remaining 57 cases, site was not reported. Conclusions: This review indicates that ultrasound is extremely reliable in diagnosing clavicle fractures in newborns and should be considered as the gold standard in this context.